Dementia care in high-income countries - Lobo, Antonio; Lobo, Elena; De-la-Cámara, Concepción (Current opinion in psychiatry, 2019)
To identify recent advances in the field of dementia care in high-income countries. New national and international initiatives identified support the notion of an increased commitment to face the challenge of dementia care. Recent research has documented barriers and facilitators to provide good care, and provided data on the specific needs of caregivers; the needs for better training of general practitioners; the negative influence of behavioural and psychological symptoms of dementia (BPSD); the palliative care needs; and the increased risk of dementia associated with anxiety (the population-attributable fraction of Alzheimer's risk was 6.1%). Significant advances in new technologies applicable in the care of dementia have also been reported. The increased awareness of the needs in dementia care is promising, although the Organisation for Economic Co-operation and Development has alerted about the limited implementation of the programmes. Barriers and facilitators identified have implications for both clinical practice and research. Particular implications for psychiatric action have the findings on BPSDs and on the preventive potential of the treatment of anxiety detected in the community. The data on palliative care needs and particularly on the advances of new technologies also have clinical implications.